RANCANG BANGUN ALAT PEMBACA DAN PELEPAS TEKANAN OTOMATIS UNTUK INSTALASI BIOGAS - , Ir. SAIBUN; , Muslikhin Hidayat, ST., MT., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Generally, reader and pressure release gas tools on a biogas installation in Indonesia, still use a simple manometer that not equipped with a pressure value viewer and must be return manually to normal condition when biogas have overproduction. Reader and pressure release gas tool based on microcontroller, is created to increase the performance of a biogas instalation. The main function of this tool is to keep biogas pressure range and be safety system in biogas instalation. Itâs consists of sensor as reader pressure, microcontroller as processor data, LCD (Liquid Crystal Display) as viewer pressure value and solenoid valve as keeper and releaser gas. The result test indicated that it can be used well at 0-30 KPa. The maximum flow release gas is 0,18 litres/seconds at 30 KPa, so this tool only can be use in biogas instalation with 9-13 m3 volume of digester.